Pengaruh Kepemimpinan Transformatif Terhadap Organisasi Pendidikan - Mohammad Hakim, Dian (Fikroh: (Jurnal Studi Islam), 2022)
Every model or style of leadership has its own characteristics. It happened because of the way how the leader leads. Is the leader uses otoriter style, democratic, or leizesfeire. All of those styles need the maximum resuld for an organization. This resuld will lead the organization to be better organization in the future. In the educational’ organization, one of the effective style of leadership is a transformative leadership. The model always move dynamically. The leader gives the examples to his follower by his charisma. While, the followers also follow the leader because of the motivation given by his leader. Therefore, a synergic relationship between the leader and the follower will happen. They will be together to carry their organization to be better. This process happens countinuoustly. Organization will be better time by time. This model of course has special character to be understood detaily. By knowing the characteristic, it is hooped can be understood its influence to the organization which always goes ahead.